Deciphering the Unexpected Binding Capacity of the Third PDZ Domain of Whirlin to Various Cochlear Hair Cell Partners. Issue 22 (6th November 2020) - Zhu, Yanlei; Delhommel, Florent; Cordier, Florence; Lüchow, Susanne; Mechaly, Ariel; Colcombet-Cazenave, Baptiste; Girault, Virginie; Pepermans, Elise; Bahloul, Amel; Gautier, Candice; Brûlé, Sébastien; Raynal, Bertrand; et al.
Abstract: Hearing is a mechanical and neurochemical process, which occurs in the hair cells of inner ear that converts the sound vibrations into electrical signals transmitted to the brain. The multi-PDZ scaffolding protein whirlin plays a critical role in the formation and function of stereocilia exposed at the surface of hair cells. In this article, we reported seven stereociliary proteins that encode PDZ binding motifs (PBM) and interact with whirlin PDZ3, where four of them are first reported. We solved the atomic resolution structures of complexes between whirlin PDZ3 and the PBMs of myosin 15a, CASK, harmonin a1 and taperin. Interestingly, the PBM of CASK and taperin are rare non-canonical PBM, which are not localized at the extreme C terminus. This large capacity to accommodate various partners could be related to the distinct functions of whirlin at different stages of the hair cell development. Graphical Abstract: Unlabelled Image Highlights: The third PDZ domain of whirlin is independent in the multi-domain organization of the Usher protein. PDZ3 of whirlin recognizes at least seven stereociliary proteins. Whirlin PDZ3 can bind both canonical and internal PDZ binding motifs. Whirlin interacts with CASK/MPP1 kinases through a new PDZ-PBM recognition mode. A unique "Lys-Phe lock" increases the rigidity of the PDZ3 binding groove.